A New Metabolism-Related Index Correlates with the Degree of Liver Fibrosis in Hepatitis C Virus-Positive Patients - Hirayuki Enomoto; Nobuhiro Aizawa; Hideji Nakamura; Ryo Takata; Yoshiyuki Sakai; Yoshinori Iwata; Hironori Tanaka; Naoto Ikeda; Tomoko Aoki; Kunihiro Hasegawa; Kazunori Yoh; Kenji Hashimoto; et al. (Gastroenterology Research and Practice)
Background. Only a few biomarkers based on metabolic parameters for evaluating liver fibrosis have been reported. The aim of this study was to investigate the relevance of an index obtained from three metabolic variables (glycated albumin: GA, glycated hemoglobin: HbA1c, and branched-chain amino acids to tyrosine ratio: BTR) to the degree of liver fibrosis in hepatitis C virus virus- (HCV-) positive patients. Methods. A total of 394 HCV-positive patients were assessed based on the values of a new index (GA/HbA1c/BTR). The index findings were used to investigate the relationship with the degree of liver fibrosis. Results. The new index showed an association with the stage of fibrosis (METAVIR scores: F0-1: 0.42 ± 0.10, F2: 0.48 ± 0.15, F3: 0.56 ± 0.22, and F4: 0.71 ± 0.30). The index was negatively correlated with three variables of liver function: the prothrombin time percentage (P<0.0001), albumin level (P<0.0001), and cholinesterase level (P<0.0001). The new index showed a higher correlation related to liver function than FIB-4 and the APRI did. In addition, the index showed a higher AUROC value than that of FIB-4 and the APRI for prediction of liver cirrhosis. Conclusion. The new metabolism-related index, GA/HbA1c/BTR value, is shown to relate to the degree of liver fibrosis in HCV-positive patients.